Assessing the Socio-Economic Effects of Improved Rural Accessibility: A Case Study of Keraniganj Upazila (IUBAT Review, 2026)
Rural road development plays a transformative role in improving livelihoods in developing countries like Bangladesh. This study evaluates the socio-economic effects of enhanced rural accessibility in two unions of Keraniganj Upazila named Jinjira and Kalindi through structured household surveys, interviews, and field observations. Results reveal that improved connectivity significantly increased household income (by 33% in Jinjira and 17% in Kalindi) and savings (by 111.6% and 86.9%, respectively). Local businesses experienced higher customer flow and income, while better roads encouraged school attendance and improved healthcare access for 53% of respondents in Jinjira and 40% in Kalindi. A paired t-test (p = 0.001) confirmed a statistically significant rise in income levels, emphasizing the role of rural connectivity in poverty reduction. However, 24% reported congestion, 22% noted rising accidents, and 20% mentioned environmental issues, underscoring emerging sustainability challenges. The study concludes that while improved accessibility enhances income, mobility, and quality of life, long-term planning should integrate safety, environmental protection, and equitable infrastructure coverage to achieve sustainable rural transformation.IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 130-153